1991
DOI: 10.1017/s0144686x00004384
|View full text |Cite
|
Sign up to set email alerts
|

Generativity in Culture Context: The Self, Death and Immortality as Experienced by Older American Women

Abstract: Theoretical approaches to conceptualising the notion of generativity have been psychologically or psychosocially based and assume generativity to be a universal phenomenon. Because psychological issues are subsumed within a cultural context, we suggest that generativity is not a universal psychological principle but rather a cultural construct. In this paper we argue that generativity must be analysed as a product of American culture and its embeddedness in individualism. Through an analysis of ethnographicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 13 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…A LTHOUGH generativity was originally explored as a psychological and developmental construct ( Erikson, 1963 ), further research explored generativity as a cultural phenomenon ( Alexander, Rubinstein, Goodman, & Luborsky, 1991 ). Culturally, generative actions are context dependent and cannot be separated from personal identity factors, such as ethnicity and gender, and from social circumstances.…”
mentioning
confidence: 99%
“…A LTHOUGH generativity was originally explored as a psychological and developmental construct ( Erikson, 1963 ), further research explored generativity as a cultural phenomenon ( Alexander, Rubinstein, Goodman, & Luborsky, 1991 ). Culturally, generative actions are context dependent and cannot be separated from personal identity factors, such as ethnicity and gender, and from social circumstances.…”
mentioning
confidence: 99%
“…Erikson thought that generativity was a fairly universal phenomenon, since it is the principle that, regardless of culture, makes people care for the next generations and accounts for the transmission of cultural values and practices from older to younger generations. However, some studies have found that generative behavior is linked to American beliefs about the nature of the self and its emphasis in individualism (Alexander, Rubinstein, Goodman, & Luborsky, 1991), while others have found a stronger emphasis on generativity in collectivistic than in individualistic cultures (Hofer, Busch, Chasiotis, Kärtner, & Campos, 2008). Clearly, more research is needed to ascertain if generativity or some or its components vary or remain stable across cultures.…”
Section: Prospects For Generativity In the Intergenerational Fieldmentioning
confidence: 97%
“…Simply put, it is a sense of pessimism about the persistence of the cultural community. In my ethnographic fieldwork as well as in more everyday interactions with Japanese Americans, particularly Nisei elders, I have heard a number of people 16 Working from a Geertzian perspective, Alexander, Rubinstein, Goodman, and Luborsky (1991) criticize Erikson for being too focused on biological procreation and argue that his concept of generativity is embedded in the American cultural value of individualism-that is, people invest in others because they unconsciously are seeking to create an enduring, continuous self that transcends death, so generativity is a culturally sanctioned form of self-absorption. While I concur with both these points, I do not believe that either is the major theme that Alexander et al assert them to be.…”
Section: Twomentioning
confidence: 99%